Integrating strength tests of amputees within the protocol of conventional clinical gait analysis: a novel approach - Heitzmann, Daniel; Günther, Michael; Becher, Benjamin; Alimusaj, Merkur; Block, Julia; Drongelen, Stefan van; Dreher, Thomas; Braatz, Frank; Wolf, Sebastian Immanuel (Biomedical engineering, 2013)
Clinical experience tells us that the lower-limb amputees are one of the patient groups who clearly suffer from a strength deficit in their involved side. However, there is no obvious evidence for the relation between the residual limb strength and walking ability in this population. Correlating the results of the conventional clinical gait analysis (CGA) with strength tests could help to find out how deficits in strength impact the amputees’ gait. In this contribution, a new device for measuring the isometric muscle strength of the hip and the knee was tested for feasibility. Three groups were tested: one group of 11 healthy subjects (29±5 years) to test the repeatability of the device, two unilateral amputees (one transfemoral for 56 years, one transtibial for 65 years), and a reference group of 17 healthy subjects (55±10 years). The new method presents an adequate technique to integrate strength testing within a standard protocol of the CGA. Results showed to be repeatable within sessions [i.e., within-day, intraclass correlation coefficient (ICC)>0.972] and between repeated measurements (i.e., day-to-day, ICC>0.765). The tested amputees showed clear deficits in maximum isometric joint moments in their most distal joint. The first results suggest evidence for a relation between the maximum isometric joint moments and gait deviations in amputees.
Gesehen am 29.03.2021